The molecular basis of atypicality in antipsychotic drug action - Lockington, Hannah J. (2025)
Dopamine D2 receptor (D2R) antagonism is thought to be the pharmacological mechanism behind the clinical efficacy of antipsychotic drugs (APDs) in treating the positive symptoms of schizophrenia. Unfortunately, D2R antagonism is also associated with extrapyramidal symptoms (EPS) that encompass a range of motor side effects. More recently developed APDs are termed ‘atypical’ based on their low propensity to cause EPS. Despite several suggested hypotheses, no single mechanism has yet to account for all cases of atypicality in clinically prescribed APDs. This thesis explored two promising molecular mechanisms recently proposed to account for APD atypicality: (1) the reduced rebinding of atypical APDs to D2R resulting in surmountable D2R antagonism and (2) the low efficacy of atypical APDs as pharmacological chaperones of D2R, resulting in reduced D2R upregulation to the cell surface.